Porphyrins Through the Looking Glass: Spectroscopic and Mechanistic Insights in Supramolecular Chirogenesis of New Self-Assembled Porphyrin Derivatives - Stefanelli, Manuela; Savioli, Marco; Zurlo, Francesca; Magna, Gabriele; Belviso, Sandra; Marsico, Giulia; Superchi, Stefano; Venanzi, Mariano; Di Natale, Corrado; Paolesse, Roberto; Monti, Donato (Frontiers in Chemistry, 2020)
The solvent driven aggregation of porphyrin derivatives, covalently linked to a L-or D-prolinate enantiomer, results in the stereospecific formation of species featuring remarkable supramolecular chirality, as a consequence of reading and amplification of the stereochemical information stored in the proline-appended group. Spectroscopic, kinetic, and topographic SEM studies gave important information on the aggregation processes, and on the structures of the final chiral architectures. The results obtained may be the seeds for the construction of stereoselective sensors aiming at the detection, for example, of novel emergent pollutants from agrochemical, food, and pharmaceutical industry.